The E domains of pentatricopeptide repeat proteins from different organelles are not functionally equivalent for RNA editing. (25th April 2013) - Chateigner‐Boutin, Anne‐Laure; Colas des Francs‐Small, Catherine; Fujii, Sota; Okuda, Kenji; Tanz, Sandra K.; Small, Ian
Summary RNA editing in plants is an essential post‐transcriptional process that modifies the genetic information encoded in organelle genomes. Forward and reverse genetics approaches have revealed the prevalent role of pentatricopeptide repeat (PPR) proteins in editing in both plastids and mitochondria, confirming the shared origin of this process in both organelles. The E domain at or near the C terminus of these proteins has been shown to be essential for editing, and is presumed to recruit the enzyme that deaminates the target cytidine residue. Here, we describe two mutants, otp71 and otp72, disrupted in genes encoding mitochondrial E–type PPR proteins with single editing defects in ccmFN2 and rpl16 transcripts, respectively. Comparisons between the E domains of these proteins and previously reported editing factors from chloroplasts suggested that there are characteristic differences in the proteins between the two organelles. To test this, we swapped E domains between two mitochondrial and two chloroplast editing factors. In all cases investigated, E domains from the same organelle (chloroplast or mitochondria) were found to be exchangeable; however, swapping the E domain between organelles led to non‐functional editing factors. We conclude that the E domains of mitochondrial and plastid PPR proteins are not functionally equivalent, and therefore that an important component of the putative editing complexes in the two organelles may be different.